Pengembangan E-Book Interaktif Berbasis Canva Pada Materi Sistem Pencernaan Manusia Untuk Siswa Kelas V Sekolah Dasar - Ayuni, Yesi; Rohana, Rohana; Hera, Treny (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2025)
His study aims to develop an interactive e-book based on Canva focused on the topic of the human digestive system, ensuring it is valid, practical, and effective as a learning medium for fifth-grade elementary school students. The research employed a Research and Development (R&D) method using the ADDIE development model, which includes five phases: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were fifth-grade students at SDN 4 Simpang Katis during the 2022/2023 academic year. Data collection techniques involved expert validation, student response questionnaires, and learning outcome tests. The validation results showed a high level of validity, with an average score of 94.44%. Student responses indicated a very high level of practicality, with an average score of 92.3%, while the effectiveness test showed an average score of 92%. The interactive ebook features content in visual formats such as text, images, and videos, which enhances students’ understanding and motivation to learn. Therefore, the interactive e-book based on Canva is considered appropriate for use as a learning tool for teaching the human digestive system in elementary school science classes